Harvest methods determine the yield and quality of Sonchus arvensis accessions cultivated in organic way - TATIK RAISAWATI; MAYA MELATI; SANDRA ARIFIN AZIZ; MOHAMAD RAFI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Raisawati T, Melati M, Aziz SA, Rafi M. 2023. Harvest methods determine the yield and quality of Sonchus arvensis accessions cultivated in organic way. Biodiversitas 24: 4110-4119. Sowthistle (Sonchus arvensisL.) is a wild plant species with high potential for medicinal uses. Nonetheless, the understanding of agronomical aspect of this species is still limited, hindering the large-scale cultivation efforts. This species has unique traits in term of leaves morphology in which it has rosette (old) leaves and upper (inflorescence) leaves which might require particular harvesting method to obtain optimal yield and quality. This study aimed to evaluate the effect of harvest methods on leaf production, total flavonoid content, antioxidant activity and flavonoid profiles of three accessions of sowthistle. The experiment used randomized complete block design with three replications. The first factor is harvesting methods namely gradual and simultaneous harvest of lower and upper leaves of sowthistle. The second factor is three accessions of S. arvensis namely Lembang, Tawangmangu, and Banjararum. The results showed that the simultaneous harvest resulted in higherleaf number by 65%, fresh weight by 55%, and dry weight by 60% compared to those of gradual harvest. However, the difference between fresh weight and dry weight of upper leaf was more determined by the accessions with Tawangmangu had the highest weight. Antioxidant activity of sowthistle in this study is not only caused by total flavonoid. Tawangmangu accession gradually harvested produced high lower leaf antioxidants, while those harvested simultaneously produced the highest total flavonoid contents and antioxidant activity of upper leaves. The results of HPLC analysis showed the flavonoid profiles of S. arvensis leaves which contain rutin, myricetin, luteolin, quercetin, kaempferol and apigenin. Kaempferol was the highest content of flavonoid in rosette and upper leaves. The findings of this study suggest that simultaneous harvesting is recommended to obtain high sowthistle production and quality.